Geotourism - Dowling, Ross Kingston; Newsome, David, 1951- (Elsevier Butterworth-Heinemann, 2006)
Geotourism is tourism surroounding geological attractions and destinations. This unique text uses a wealth of case studies to discuss the issues involved in the management and care of such attractions, covering topics such as sustainability, impacts and environmental issues. Geotourism: Sustainability, impacts and management leads the reader logically through the process, covering both the theories involved and the practicalities of managing such 'environmentally precious' attractions.